2013
DOI: 10.1210/jc.2012-4132
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Signature Shift in Type 2 Diabetes Mellitus Revealed by Mass Spectrometry-based Metabolomics

Abstract: Using 2 highly sensitive metabolomic techniques, we report distinct serum profile change of a wide range of metabolites from healthy persons to type 2 diabetes mellitus. Apart from glucose, IFG and diabetes mellitus are characterized by abnormalities in amino acid, fatty acids, glycerophospholipids, and sphingomyelin metabolism. These early broad-spectrum metabolic changes emphasize the complex abnormalities present in a disease defined mainly by elevated blood glucose levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
167
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(210 citation statements)
references
References 20 publications
39
167
4
Order By: Relevance
“…Sphingomyelins are generated by virtue of both salvage and de novo ceramide pathways (37), which may be relevant to their debated role in health and disease. Epidemiologic data demonstrate a positive correlation between total serum sphingomyelin concentration and CVD (18,29), yet total serum sphingomyelin has been reported as lower in CVD-prone states such as obesity, type 1 diabetes, and type 2 diabetes (35,39). Metabolomic profiling has helped clarify this discrepancy by associating certain sphingomyelin species, rather than total concentration, with metabolic parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Sphingomyelins are generated by virtue of both salvage and de novo ceramide pathways (37), which may be relevant to their debated role in health and disease. Epidemiologic data demonstrate a positive correlation between total serum sphingomyelin concentration and CVD (18,29), yet total serum sphingomyelin has been reported as lower in CVD-prone states such as obesity, type 1 diabetes, and type 2 diabetes (35,39). Metabolomic profiling has helped clarify this discrepancy by associating certain sphingomyelin species, rather than total concentration, with metabolic parameters.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of dietary survey data, it is unclear if this identified trend in erythritol levels was due to increased consumption of sweeteners or DR-related metabolic dysregulation. Mannose, a metabolite in galactose metabolism, was previously identified as a marker for impaired fasting glucose (14,15) and diabetes (14,20). Increased plasma levels of mannose were identified in DR cases from discovery metabonomic profiling ( Fig.…”
Section: Metabonomic Profiling Identifies Dr-associated Pathwaysmentioning
confidence: 97%
“…2-Hydroxybutyric acid, a derivative of a-ketobutyrate, was previously identified as a marker (14,21) and predictor (44) for diabetes. The ketone body, 3-hydroxybutyric acid, was identified as a marker for impaired glucose tolerance (13) and type 2 diabetes (20,21) and was also identified as a marker for DR in the study by Li et al (26).…”
Section: Unique Signatures Of Hydroxy Fatty Acids In Drmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent metabolomics studies have suggested that certain metabolites and metabolite classes may be associated with the risk of obesity, insulin resistance and type 2 diabetes [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. The Framingham Offspring Study, a 12-year prospective cohort study, has shown that increases in certain branched-chain amino acids (BCAAs) (such as leucine, isoleucine and valine) and aromatic amino acids (AAAs) (such as tyrosine and phenylalanine) could predict the incidence of type 2 diabetes [6].…”
Section: Introductionmentioning
confidence: 99%